Feeding frequency and rate during feed training of Pacamã juveniles - Silva, Walisson de Souza e; Cordeiro, Nelmara Inês Santos; Costa, Deliane Cristina; Takata, Rodrigo; Luz, Ronald Kennedy (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate feeding frequency and rate during feed training of pacamã juveniles. Feeding for three or four times a day and the feeding rates at 50, 75 and 100% of biomass were tested. Feeding management did not affect fish growth, survival, mortality, and cannibalism. Lack of management effect was kept when animals were fed extruded feed threefold a day, during 30 days. Feeding rate at 50% of biomass and threefold‑a‑day feeding can be used for the feed training of pacamã juveniles.